Kepastian Hukum Terhadap Penggunaan Digital Signature Sebagai Alat Bukti Dalam Perjanjian Umum - Panji Ali Candra; Jeane Neltje; Diana Fitriana (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The use of electronic documents signed with electronic signatures as evidence is different from evidence regulated in the Civil Code, because the level of originality or authenticity still needs to be proven first, or in other words has objections to electronic evidence that has legal force, this study aims to know the validity of electronic signatures in proving Indonesian civil procedural law, as well as to determine efforts to resolve civil disputes on electronic documents signed with electronic signatures. This writing uses normative legal research, utilizing existing legal literature and its relation to the problem to be studied. The conclusion of this study is that electronic signatures are valid when using electronics in accordance with applicable laws and regulations, namely the Law on Electronic Information and Transactions Article 16 Paragraph (1), expert testimony is also one of the elements considered important for the examination process because it provides an explanation regarding the authenticity or authenticity of evidence which is an electronic signature submitted.